Effectiveness of automated appointment reminders in psychosis community services: a randomised controlled trial - Eugenia Kravariti; Christopher Reeve-Mates; Rafaela Da Gama Pires; Elias Tsakanikos; Daniel Hayes; Siobhan Renshaw; Sarah McAllister; Vishal Bhavsar; Pam Patterson; Emily Daley; Jane Stewart; Megan Pritchard; et al. (BJPsych Open, 2018)
We report on the first open-label, parallel group randomised controlled trial of automated appointment reminders in a psychosis community service in the UK. Ninety-five patients were randomly allocated to receiving/not receiving automated messaging reminders 7 days and 1 day before appointments. All ‘Attended’ and ‘Missed’ appointment outcomes over 6 months were analysed using cluster regression analysis. Reminded appointments were significantly more frequently attended than non-reminded appointments (unadjusted odds ratio (OR) = 3.54, 95% CI 1.36–9.22, P = 0.01; adjusted OR = 2.95, 95% CI 1.05–8.85, P < 0.05). Automated messaging reminders can provide a robust strategy for promoting engagement with psychosis services.